Pengendalian Kualitas Produk dengan Metode Control Chart pada PT XYZ - Muktiadji, Nusa; Hidayat, Lukman (Jurnal Ilmiah Ranggagading (JIR), 2006)
This research was conducted to find out quality control process thatâs carried out by production unit and control chart method implementation by firm to increase product quality. The main variables were product as independent variable and quality as dependent variable. Data processing analysis was done by SQC technique with control chart method for attribute based on reject full percentage. Keywords: Control Chart; Product Quality Control.